Acute Tolerance to Alcohol in At-risk Binge Drinkers - Fillmore, Mark T. (2011)
Studies of the impairing effects of alcohol on behavior often show greater tolerance in heavy drinkers compared to light drinkers, suggesting a causal link between heavy consumption and tolerance. Tolerance also develops during the time-course of a single drinking episode, and this “acute tolerance” might play an important role in the escalation to heavy drinking. The present study examined the development of acute tolerance to the impairing effects of alcohol on motor coordination and inhibitory control in a group of at-risk, binge drinkers (N = 20) and a group of non-risk, moderate drinkers (N = 20). Participants performed the testing battery in response to placebo and a moderate dose of alcohol (0.65 g/kg) twice at comparable blood alcohol concentrations (BACs): once on the ascending limb and once on the descending limb of the blood alcohol curve. Results showed marked acute tolerance to the impairing effects of alcohol on motor coordination in the at-risk drinkers. By contrast, no recovery of motor skill was observed in the non-risk drinkers. Regarding inhibitory control, both groups remained impaired on both the ascending and descending limbs, indicating no acute tolerance in either group. The findings suggest that at-risk, binge drinkers display a faster recovery in their ability to execute versus inhibit action under alcohol. Such an “activational bias” of behavior could account for their continued alcohol consumption and impulsive behaviors while intoxicated, especially as BAC begins to decline.